PENGARUH KUALITAS PELAYANAN, SANKSI PAJAK ,DAN PENGETAHUAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN: Studi Kasus pada Wajib Pajak Bumi dan Bangunan di Badan Pendapatan Daerah Kota Denpasar - Ayu Kade Restu Pebrianti Dewi; Made Yudi Darmita; Ni Made Wiwekandari (Journal Research of Accounting, 2021)
This study aims to determine the effect of service quality, tax sanctions, and knowledge of taxpayers on taxpayer compliance. The location of this research is the Regional Revenue Agency of Denpasar City. The sample in this study was 100 respondents. The data analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that the service quality of tax officers has a positive effect on taxpayer compliance at the Denpasar City Government Regional Revenue Agency. Tax sanctions have a positive effect on taxpayer compliance at the Denpasar City Government Regional Revenue Agency. Taxpayer knowledge has a positive effect on taxpayer compliance at the Denpasar City Government Regional Revenue Agency.